Effectiveness of Cognitive-Behavioral Therapy on Reducing Impulsive Behaviors, Alexithymia, and Despair in Depressed Patients at Counseling Centers in Ahvaz: Alexithymia and Despair in Depressed Patients - Sedighrad 1, Gholamreza; Asgari 2*, Parviz; Heidari 2, Alireza; Seraj Khorami 3, Naser (Shahroud Journal of Medical Sciences, 2021)
Background: Depression is one of the most prevalent mental disorders that severely affect activities and mental health. The present study aimed to investigate the effectiveness of cognitive-behavioral therapy (CBT) on reducing impulsive behaviors (IBs), alexithymia, and despair in depressed patients at counseling centers in Ahvaz.Methods: The research method was quasi-experimental with a pre-test, post-test, and one-month follow-up design, and a control group. The study population comprised all patients with depression who were referred to the counseling centers of Ahvaz in 2019. The sample consisted of 30 patients with depression selected by convenience sampling and divided into experimental and control groups (n= 15 per group). The experimental group underwent twelve sessions (90-minutes sessions per week) of cognitive-behavioral therapy. The research instruments included the Barratt Impulsiveness Scale (BIS), the Toronto Alexithymia Scale (TAS-20), and the Miller Hope Scale (MHS). The follow-up was performed after 30 days. Data were analyzed using multivariate analysis of covariance (MANCOVA).Results: The results showed that cognitive-behavioral therapy (CBT) reduced impulsive behaviors (IBs), alexithymia, and despair in the experimental group of depressed groups compared with the control group in the post-test and follow-up (Pvalue= 0.0001).Conclusions: CBT can be used at counseling centers for better treatment of IBs, alexithymia, and despair in depressed groups.Keywords: Cognitive-behavioral therapy, Impulsive behaviors, Alexithymia, Despair, Depression.